Inovasi Dan Problematika Pelaksanaan PP 48 Tahun 2014 Tentang Biaya Nikah (Studi Di Lingkungan Kantor Kementerian Agama Kota Batu) - Dicky Sidharta Agustia Putra; M. Mas'ud Said; Afifuddin Afifuddin (Ji_Mild (Jurnal Ilmiah Magister Ilmu Administrasi), 2021)
AsbtractThe research begins in the circumstance of the implementation of PP 48/2014 concerning Amendments to PP Number 47/2004 concerning Tariffs on Types of Non-Tax State Revenues Applicable to the Ministry of Religion regarding radical changes in the cost of recording marriage events because they immediately change the nominal value drastically. The main idea in this study is how the implementation of the process of managing the cost of recording marriage event in the implementation of PP 48/2014, innovation in the application and use of information technology in assisting the implementation of PP 48/2014 and solutions for implementing the use of IT in recording costs of marriage events according to PP 48/2014. Qualitative method with a descriptive approach was used in this research. This research took place in Batu City, especially at the Ministry of Religious Affair of Batu City and more specifically at the subdistrict religious affairs office in Batu City. Data collection technique that used in this research is field research. For analyzing data method, begian with checking the data, organizing the data, interpreting the data, discussing and formulating the results of the interpretation, and took final conclusions. The results of the study show that the implementation of Government Regulation Number 48 of 2014 at the Office of the Ministry of Religion of Batu City, found a management process that starts with the socialization stage to the accountability of use that was straight with the rules. The results also found innovations at the level of activities and programs such as the Binwin Online Program, BKS Activities. As well as innovations in information technology and digitalization of services such as marriage payments and online marriage registration and the issuance of marriage cards. The results also show that the emergence of problems has been followed up with innovation as a solution, such as the use of digitalyze applications system for recording the management of marriage costs that can be accessed in real time from the highest level to lowest level. The mainconclusion that can be suggested from the results of this study are to intensify the efforts of the Ministry of Religion Office of Batu City to improve existing an an unique innovations as a form of service improvement. Keywords: costs of marriage event, innovation, problematics